2023
DOI: 10.11591/ijece.v13i2.pp2131-2141
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of variational iteration method for various types of linear and nonlinear partial differential equations

Abstract: There are various linear and nonlinear one-dimensional partial differential equations that are the focus of this research. There are a large number of these equations that cannot be solved analytically or precisely. The evaluation of nonlinear partial differential equations, even if analytical solutions exist, may be problematic. Therefore, it may be necessary to use approximate analytical methodologies to solve these issues. As a result, a more effective and accurate approach must be investigated and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These formulas are an important improvement and provide accurate and powerful solutions to Riemann-Liouville fractional derivatives. A study by Shihab et al [16] showed the use of the method of variational iteration in solving several types of partial differential equations, whether linear or nonlinear. In this study, it was shown that the Lagrange multiplier can be used to determine an ideal value of parameters in a functional form, and then use these values to construct an iterative series solution.…”
Section: Introductionmentioning
confidence: 99%
“…These formulas are an important improvement and provide accurate and powerful solutions to Riemann-Liouville fractional derivatives. A study by Shihab et al [16] showed the use of the method of variational iteration in solving several types of partial differential equations, whether linear or nonlinear. In this study, it was shown that the Lagrange multiplier can be used to determine an ideal value of parameters in a functional form, and then use these values to construct an iterative series solution.…”
Section: Introductionmentioning
confidence: 99%